Some Customary Law Nuance on that Hagiography: Attempt of Interpretations - Marius Ščavinskas (Lietuvos Istorijos Studijos)
Early sources about vendetta custom are some papers of the German Order provided in the XIII century. Some of these customs reflect in the Statutes of Lithuania, in some judicial cases of the XVI century, and in modified law records of other Baltic tribes, first of all in the Prussian Pamedė statute-book (XIV). But we can also find vendetta custom in hagiographical sources of late X-early XI centuries, sacred for St. Wojciech and St. Brunon of Querfurt martyrdom in Baltic lands.